2022
DOI: 10.1071/es21015
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic ozone hole during 2020

Abstract: The Antarctic ozone hole remains the focus of scientific attention because of its importance to the health of the biosphere and its influence on the climate of the southern hemisphere. Here we examine the general characteristics of the 2020 Antarctic ozone hole using a variety of observational and reanalysis data and compare and contrast its behaviour with earlier years. The main feature of the 2020 ozone hole was its relatively large size, and persistence to the beginning of the 2020/2021 summer, with new max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…These conditions led to the longest-lived Antarctic ozone hole in the observational record. Consequently, record-low total ozone columns in November and December 2020 resulted in unusually high levels of UV-B radiation (280-315 nm) in the Antarctic region [8,10]. At Arrival Heights (78° S), the UV index (UVI) reached a new all-time site record of 7.8 on 23 December (Fig.…”
Section: The 2020 Antarctic Ozone Hole Led To Record-breaking Increas...mentioning
confidence: 99%
“…These conditions led to the longest-lived Antarctic ozone hole in the observational record. Consequently, record-low total ozone columns in November and December 2020 resulted in unusually high levels of UV-B radiation (280-315 nm) in the Antarctic region [8,10]. At Arrival Heights (78° S), the UV index (UVI) reached a new all-time site record of 7.8 on 23 December (Fig.…”
Section: The 2020 Antarctic Ozone Hole Led To Record-breaking Increas...mentioning
confidence: 99%
“…Nevertheless, it appears likely that the combined effects of climate change and ozone depletion could have impacted both the timing and magnitude of these wildfires with considerable consequences for ecosystems in this region. In contrast to 2019, a strong and persistent Antarctic ozone hole occurred in 2020 and 2021 [ 54 , 74 76 ] and this led to record surface UV irradiances at several sites across East Antarctica during early summer. It has been suggested that the Australian wildfires that occurred during the previous summer contributed to this strong ozone loss [ 18 , 54 – 56 , 71 , 72 , 74 ].…”
Section: Effects Of Stratospheric Ozone Depletion On Climate and Extr...mentioning
confidence: 99%
“… In contrast to 2019, a strong and persistent Antarctic ozone hole occurred in 2020 and 2021 [ 54 , 74 76 ] and this led to record surface UV irradiances at several sites across East Antarctica during early summer. It has been suggested that the Australian wildfires that occurred during the previous summer contributed to this strong ozone loss [ 18 , 54 – 56 , 71 , 72 , 74 ]. There is evidence that increased ozone depletion has tended to delay the annual breakdown of the Antarctic stratospheric vortex [ 77 ].…”
Section: Effects Of Stratospheric Ozone Depletion On Climate and Extr...mentioning
confidence: 99%
“…Significant minor Antarctic stratospheric warmings occurred in September 1988 (Kanzawa & Kawaguchi, 1990) and September 2019(Yamazaki et al, 2020Milinevsky et al, 2020;Smale et al, 2021;Roy et al, 2022). The warming in 2019 is particularly significant because it came close to reversing the zonal wind at 10 hPa (Rao et al, 2020;Liu et al, 2022), and the stratospheric disturbance has been shown to have significant influences on the Quasi-Biennial Oscillation (QBO) (Anstey et al, 2021) as well as the climate in parts of the Southern Hemisphere, particularly Australia (Lim et al, 2021;Klekociuk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the QBO was in an easterly phase which would also tend to weaken the vortex (Baldwin & Dunkerton, 1998;Klekociuk et al, 2021). On the contrary, in 2020, the prevailing climate modes included a developing La Niña and a westerly QBO (Klekociuk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%